Organ Donation in Islam: A Search for a Broader Quranic Perspective - Islam, Tazul (Religions, 2021)
Organ donation is a widely debated issue in Islamic scholarship. Muslim jurists, however, have produced a substantial amount of evidence supporting its legality. Despite this, previous research has revealed that Muslim communities around the world are still wary of organ donation. The main reasons for this attitude are motivational and educational in nature. To address these two problems, the purpose of this research is to look into the Quranic conceptual background, which could help to expand the justification of organ donation in the motivational context. This study investigated the Quranic verses that scholars have cited in their writings on organ donation and transplantation. The theoretical underpinnings for the use of those verses were deduced. Data were collected from 36 studies on organ donation that refer to Quranic verses and examined how those verses were analyzed. This study discovered that a number of Quranic verses were primarily used to justify the permissibility of organ donation, with little effort made to analyze the verses using specific methodologies dedicated to the Quranic texts. As a result, the outcome may not be helpful to solve the current dilemma which is Muslim communities’ reluctance to donate organs. Hence, it is important to explore a broad theoretical framework for organ donation based on the Quran. This study suggests how to bring this new perspective to the subject and overcome the existing problem.